Iloprost improves running performance at 5,000 m in Han but not in Tibetans - Bengt Kayser; Jui-Lin Fan; Liya Nan; Wang Liang Bang; Bianba; Tianyi Wu (Bern Open Publishing, 2019)
Background: Tibetans experience lose less aerobic exercise capacity in hypoxia compared to lowland Han. We tested if inhalation of iloprost (to counter hypoxic pulmonary vasoconstriction) and furosemide (to decrease afferent vagal traffic from pulmonary receptors) improve performance in hypoxia in Han compared to Tibetans. Methods: 8 Tibetans and 8 Han, living at 2,260 m, did incremental uphill treadmill running to exhaustion at ambient pressure on day 1, followed by three runs at 5,000 m (hypobaric chamber) after inhalation of iloprost (ILO), furosemide (FUR) or placebo (PLA), on different days in a counter-balanced order. Results: In Han the performance decrement from 2,260 m to 5,000 m was greater than in Tibetans (p<0.05). In Han iloprost improved performance at 5,000 m compared to placebo (p<0.05 vs. PLA); furosemide had no effects. In Tibetans there were no treatment effects. Peripheral O2saturations at peak exercise at 5,000 m, were higher by ～8 % in the Tibetans (p<0.05 vs. Han). Maximum heart rate was lowered by 13±6 bpm in Han at 5,000 m regardless of treatment compared to 2,260 m (p<0.05). Tibetans reached similar maximum heart rates ∼200 bpmat 5,000 m and 2,260 m, independent of treatment. Conclusions: The blunting of the exercise impairment in severe hypoxia in Han during maximal exercise after inhalation of iloprost suggests that hypoxic pulmonary vasoconstriction and right ventricular function are potential performance limiting factors in Han in hypoxia.